Socioeconomic inequalities in hospital births in China between 1988 and 2008 - Xing Lin Feng; Ling Xu; Yan Guo; Carine Ronsmans (The World Health Organization, 2011)
OBJECTIVE: To assess trends in hospital births in China during 1988-2008 in an effort to determine if efforts to overcome financial barriers to giving birth in hospital have reduced the access gap between the rich and the poor. METHODS: Cross-sectional data obtained from four National Health Service Surveys were used to determine trends in hospital births during 1988-2008. Crude and adjusted annual rates were calculated by means of Poisson regression and were used to define trends across socioeconomic regions and households in different income quintiles. FINDINGS: In 2008 women throughout China were giving birth in hospital almost universally except in region IV, the most remote rural region, where the percentage of hospital births was only 60.8. Hospital births in this region had increased steadily before 2002, but after that year the upward trend slowed down. During 1988-2001 the average yearly increase had been 21%, but in 2002-2008 it dropped to 10% (P=0.0031). Inequalities between socioeconomic regions were greater than among individual households belonging to different income strata. By 2008 the difference between low- and high-income households in the proportion of hospital births had become very small (96.1% and 87.7% of high- and low-income households, respectively, gave birth in hospital that year). CONCLUSION: Most Chinese women now give birth in hospital, but the poorest rural region is still lagging behind. A more active and comprehensive approach will be needed to increase hospital births in these remote, hard-to-reach populations.